La aplicación del artículo 42 de la Ley de Inquilinato y el derecho de los arrendatarios a la tutela judicial efectiva. - Soldado García, Ana Lucia (2023)
This investigation, "The Application of Article 42 of the Tenant Law and the Right of Tenants to Effective Judicial Protection," has originated because, at the time of filing the appeal by the tenant must comply with the consignment of the values of the rented pensions owed, causing access to the appeal to be prevented. This right is guaranteed in the Constitution of the Republic of Ecuador as well as in various International Treaties and Agreements. In this regard, this investigation aims to describe whether or not this aspect affects the effective judicial protection of the appellant. For compliance, the investigation was developed in two parts: first, through the treatment of the consistent theoretical framework in 3 units called: the first, dispute processing. The second is adequate judicial protection, and the third is the proportionality test. The methodological design appropriate to a social, legal investigation was developed through the legal-doctrinal, legal-analytical, inductive, descriptive research method; qualitative research approach; types of bibliographic and descriptive research; non-experimental research design. Additionally, information has been collected thanks to the research instruments, allowing conclusions and recommendations to be drawn according to the problem investigated.